2019
DOI: 10.1038/s41598-018-37269-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficient curation of genebanks using next generation sequencing reveals substantial duplication of germplasm accessions

Abstract: Genebanks are valuable resources for crop improvement through the acquisition, ex-situ conservation and sharing of unique germplasm among plant breeders and geneticists. With over seven million existing accessions and increasing storage demands and costs, genebanks need efficient characterization and curation to make them more accessible and usable and to reduce operating costs, so that the crop improvement community can most effectively leverage this vast resource of untapped novel genetic diversity. However,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
94
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 40 publications
3
94
1
1
Order By: Relevance
“…Among 1109 ginseng accessions, 167 (15.1%) (12 accessions in CN, five accessions in CB, and 133 accessions in NIHHS) might be duplicated ( Table 2). It is important to identify these duplicated accessions, due to the limitation of funding and resources in genebanks [45]. Although not all duplicate accessions are worthless, identifying unique accessions within and across the genebanks will facilitate the better use of plant germplasms [45,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 1109 ginseng accessions, 167 (15.1%) (12 accessions in CN, five accessions in CB, and 133 accessions in NIHHS) might be duplicated ( Table 2). It is important to identify these duplicated accessions, due to the limitation of funding and resources in genebanks [45]. Although not all duplicate accessions are worthless, identifying unique accessions within and across the genebanks will facilitate the better use of plant germplasms [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to identify these duplicated accessions, due to the limitation of funding and resources in genebanks [45]. Although not all duplicate accessions are worthless, identifying unique accessions within and across the genebanks will facilitate the better use of plant germplasms [45,46]. In this study, 167 ginseng accessions identified will also require the management of duplicate accessions using various additional methods such as evaluation of morphological and/or biochemical traits.…”
Section: Discussionmentioning
confidence: 99%
“…These landraces constitute reservoirs of genetic diversity that can be directly cross‐bred into modern cultivars. There are thousands of these landrace accessions available; however, many of them are heterogeneous, often duplicated seed stocks (Singh et al ., ), which remain confined to germplasm repositories. Of special note is the Watkins landrace collection (Wingen et al ., ) encompassing over 1000 landraces collected in the 1920s and 1930s from a wide geographic distribution.…”
Section: Use Of Natural Variation For Trait Discoverymentioning
confidence: 99%
“…Collections are sometimes large: 21,393 accessions of Hordeum vulgare at the Leibniz-Institut für Pflanzengenetik und Kulturpflanzenforschung (IPK), 53,777 accessions of Sorghum bicolor in the US National Plant Germplasm System (NPGS), 124,378 accessions of Oryza sativa at the International Rice Research Institute (IRRI). Within a species, genetic diversity is unevenly partitioned across accessions, with ample evidence of redundancy [38,39]. Phenotypic characterization may also be uneven ( Figure 5).…”
Section: Discussionmentioning
confidence: 99%